A Case of a Gunshot Wound with 5.7 × 28 mm Ammunition. Issue 2 (June 2013) - Poulos, Christopher K.
The 5.7 × 28 mm family of cartridges was designed by Fabrique Nationale in Belgium as a military cartridge designed to penetrate body armor while still being fired from a small personal defense weapon that could be carried by military personnel whose activities precluded carrying larger weapons. To accomplish this, the designers relied upon a projectile with a steel penetrator and extremely high velocities. As hollow point ammunition is forbidden from military use by the Hague Convention, the projectile was designed to deposit its energy within the body by yawing (tumbling) rather than expanding or deforming. Since its introduction, civilian variants of the 5.7 × 28 mm cartridge have been developed, and while the projectiles of these cartridges are not armor piercing, some appear to retain the yawing characteristics of the military projectiles as illustrated in the case of an individual shot with a civilian variant of the 5.7 × 28 mm cartridge where the yaw was evidenced by the rear-first positioning of the projectile when recovered at autopsy.